Applications of IoT and Artificial Intelligence in Water Quality Monitoring and Prediction: A Review - Mustafa H.M.; Mustapha A.; Hayder G.; Salisu A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Backpropagation; Decision making; Forecasting; Gradient methods; Linear systems; Nonlinear programming; Predictive analytics; Radial basis function networks; Sewage treatment plants; Wastewater treatment; Water quality; Broyden-Fletcher-Goldfarb-Shanno; Feedforward backpropagation; Internet of Things (IOT); Modeling and forecasting; Radial basis function neural networks; Wastewater treatment plants; Water quality monitoring; Water quality parameters; Internet of things